2012
DOI: 10.1021/ic301172g
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Spectroscopic Study of Ce(III) Coordination in the 1-Butyl-3-methylpyrrolidinium Bis(trifluoromethylsulfonyl)imide Ionic Liquid Containing Chloride Ion

Abstract: Cyclic staircase voltammetry, controlled potential coulometry, and electronic absorption spectroscopy were used to probe the coordination and accessible oxidation states of Ce(3+) dissolved in the ionic liquid 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide (BuMePyroTf(2)N) before and after the addition of chloride ion as BuMePyroCl. Controlled potential coulometry indicated that the oxidation of Ce metal in this ionic liquid produces only Ce(3+). Spectroscopic examination of the resulting solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 44 publications
6
47
0
Order By: Relevance
“…[11] In contrast,I Lw ere shownt ob eg ood solvents for the stabilization and study of the oxidation states + II and + IV for Ln. [12][13][14][15] Specifically,E u II can be stabilized in aqueous solutions thanks to cyclic ligands such as cryptands or analogues [16] whereasi nn onaqueousm edia, fully dissolved stablef orms of Ln II can be observed. [17,18] The electrochemical behavior of the Eu III /Eu II redoxc ouple was extensively studiedi nawide range of IL [14,[19][20][21][22][23][24][25][26][27] and its apparent standard potential was found to vary between0and À1.0 Vv ersus ferrocenium/ferrocene (Fc + /Fc) reference, depending on the medium.…”
Section: Introductionmentioning
confidence: 99%
“…[11] In contrast,I Lw ere shownt ob eg ood solvents for the stabilization and study of the oxidation states + II and + IV for Ln. [12][13][14][15] Specifically,E u II can be stabilized in aqueous solutions thanks to cyclic ligands such as cryptands or analogues [16] whereasi nn onaqueousm edia, fully dissolved stablef orms of Ln II can be observed. [17,18] The electrochemical behavior of the Eu III /Eu II redoxc ouple was extensively studiedi nawide range of IL [14,[19][20][21][22][23][24][25][26][27] and its apparent standard potential was found to vary between0and À1.0 Vv ersus ferrocenium/ferrocene (Fc + /Fc) reference, depending on the medium.…”
Section: Introductionmentioning
confidence: 99%
“…A number of reports have addressed the electrochemical deposition of rare earth metals from ionic liquids (29)(30)(31)(32)(33)(34)(35). The electrodeposition of RE metal from RE 3+ ions is often not a single step process but involves the intermediate formation of a lower valency species (36)(37)(38) which is stable for some RE/IL combinations, and disproportionates to metal and RE 3+ for others (36)(37)(38)(39). Especially in butylmethylpyrrolidinium bistrifluoromethylsulfonylimide (BMP TFSI), surface passivation instead of metal deposition was observed for a number of RE metals, like Ce, Pr and Nd (36,37).…”
Section: Introductionmentioning
confidence: 99%
“…The electrodeposition of RE metal from RE 3+ ions is often not a single step process but involves the intermediate formation of a lower valency species (36)(37)(38) which is stable for some RE/IL combinations, and disproportionates to metal and RE 3+ for others (36)(37)(38)(39). Especially in butylmethylpyrrolidinium bistrifluoromethylsulfonylimide (BMP TFSI), surface passivation instead of metal deposition was observed for a number of RE metals, like Ce, Pr and Nd (36,37). Many studies on RE metal deposition were characterized by the absence of a corresponding dissolution peak (30,33,34,40), which is explained by slow charge transfer kinetics or reactions with residual moisture (33) or the ionic liquid (34).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the electrochemistry of Cerium (III) has been studied in the basic AlCl 3 -1-methyl-3-ethylimidazolium chloride [21] and in 1-butyl-3-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide containing chloride ions [2], in both cases, it is reported that Ce(III) (i.e. CeCl 6 3 − ) is oxidized to Ce(IV) (i.e.…”
Section: Introductionmentioning
confidence: 99%